KESIAPAN GURU SEKOLAH DASAR DALAM MENERAPKAN MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) DI KEPENGHULUAN PASIR LIMAU KAPAS - Muhammad Zamzuri; Suripah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the readiness of elementary school teachers in implementing the PBL (problem based learning) learning model in Kepenghuluan Pasir Limau Kapas. This study was conducted in Kepenghuluan Pasir Limau Kapas.The process of data collection and data collection is carried out online via google form using a questionnaire and using a quantitative descriptive research method. The researcher used non-probability sampling as a sample, the number of samples was 20 teachers. The analysis of this research used descriptive percentage analysis. The results of the study are that teachers are ready to implement the PBL (Problem Based Learning) learning model in Kepenghuluan Pasir Limau Kapas in the form of (1). Understanding the characteristics of the learning model. (2). Readiness of the learning plan. (3). Implementation of learning. (4). Facilities and infrastructure.